Ashamed Caregivers: Self-Stigma, Information, and Coping among Dementia Patient Families. Issue 11 (1st November 2020) - Jeong, Jae-Seon; Kim, Soo Yun; Kim, Jeong-Nam
Abstract : The number of people living with dementia increases almost every year, and the majority of the care system for these individuals is often made up of close family members. This study investigates the relationship between family caregivers' cross-checking of information with healthcare providers and patient health outcomes. Specifically, we examined whether this relationship was mediated by caregivers' enhanced coping efficacy. We also tested the moderation effect of family caregivers' affiliate stigma on information cross-checking, coping efficacy, and coping outcomes. Using a survey of 226 family caregivers of dementia patients in South Korea, this study tested the moderated mediation model with the PROCESS macro. Results indicate that low affiliate stigma moderates coping efficacy on the relationship between information cross-checking and dementia patients' health outcomes. Further implications for family caregiving and general dementia care are discussed.